2017
DOI: 10.1111/jocn.13722
|View full text |Cite
|
Sign up to set email alerts
|

‘Just not for me’ – contributing factors to nonattendance/noncompletion at phase III cardiac rehabilitation in acute coronary syndrome patients: a qualitative enquiry

Abstract: Aims and objectives To explore what reasons do nonattenders and noncompleters give for their patterns of participation or nonparticipation in cardiac rehabilitation programmes and how future uptake could be enhanced. Background Cardiac rehabilitation is a cost‐effective clinical intervention designed for adults with acute coronary syndrome. Despite evidence from meta‐analyses demonstrating that cardiac rehabilitation programmes facilitate physical and psychological recovery from acute coronary syndrome, only 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 41 publications
(66 reference statements)
5
44
0
3
Order By: Relevance
“…Consistent with our findings, other studies have found a positive correlation between coherence and physical health but in [15]. Consistent with Cooper et al [29,45], and Herber et al [69], we identified that the patients' perceived significant barriers to CR, but quality of life was not assessed in these studies. We identified the patient's perceptions of control (B-IPQ) did not significantly predict their physical health (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, other studies have found a positive correlation between coherence and physical health but in [15]. Consistent with Cooper et al [29,45], and Herber et al [69], we identified that the patients' perceived significant barriers to CR, but quality of life was not assessed in these studies. We identified the patient's perceptions of control (B-IPQ) did not significantly predict their physical health (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…This can be supported through a course of cardiac rehabilitation offered through the national health service (NHS), though uptake is low [18]. Whilst there are many reasons why this may be the case [19][20][21][22], some of it may be due to inadequate levels of health literacy.…”
Section: Health Literacy and Cardiovascular Diseasementioning
confidence: 99%
“…Recent figures have highlighted that the UK has internationally leading levels of uptake, despite still falling short of national recommendations 8. Current evidence suggests that perceived barriers to traditional, centre-based CR may include practical barriers, personal or programme factors 9. Therefore, the future of CR requires flexible delivery and personalisation of care,6 while being mindful of organisational and financial constraints.…”
Section: Introductionmentioning
confidence: 99%